2006
DOI: 10.1182/blood-2005-11-011932
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A is an innate immune opsonin for Gram-negative bacteria

Abstract: Serum amyloid A (SAA) is the major acutephase protein in man and most mammals.Recently we demonstrated that SAA binds to many Gram-negative bacteria including Escherichia coli and Pseudomonas aeruginosa through outer membrane protein A (OmpA) family members. Therefore we investigated whether SAA altered the response of innate phagocytic cells to bacteria. Both the percentage of neutrophils containing E coli and the number of bacteria per neutrophil were greatly increased by SAA opsonization, equivalent to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
165
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(171 citation statements)
references
References 36 publications
2
165
0
4
Order By: Relevance
“…SAA1 and pro-inflammatory chemokines IL8, CCL2, CXCL5, CXCL3, CXCL2 and CCL8 belong to the top-ten most up-regulated genes (see Table 3), SAA1 being the most up-regulated gene with a 27-fold change by comparison to mock-stimulated PBMCs. SAA1 encodes the major acute-phase protein Serum Amyloid A (SAA), the precise role of which is still unclear despite reports suggesting a key role in the establishment and maintenance of inflammation notably as an antiapoptotic agent for neutrophils [36] and as an opsonin that would facilitate phagocytosis of gram-negative bacteria [37]. SAA1 was also found as the most up-regulated gene in spleen seven days after infection by H. parasuis [9].…”
Section: Discussionmentioning
confidence: 99%
“…SAA1 and pro-inflammatory chemokines IL8, CCL2, CXCL5, CXCL3, CXCL2 and CCL8 belong to the top-ten most up-regulated genes (see Table 3), SAA1 being the most up-regulated gene with a 27-fold change by comparison to mock-stimulated PBMCs. SAA1 encodes the major acute-phase protein Serum Amyloid A (SAA), the precise role of which is still unclear despite reports suggesting a key role in the establishment and maintenance of inflammation notably as an antiapoptotic agent for neutrophils [36] and as an opsonin that would facilitate phagocytosis of gram-negative bacteria [37]. SAA1 was also found as the most up-regulated gene in spleen seven days after infection by H. parasuis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SAA has been shown to bind to the outer membrane protein A of a large number of Gram-negative bacteria and to be involved in opsonization of these bacteria. 32,33 The observations that SAA binds to HCV and has an antiviral activity against this virus provide experimental evidence that SAA can have a direct effect against pathogens. This observation is in favor of a role for SAA in the innate immune response against HCV.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial SAA protein is an opsonin for gram-negative bacteria (Shah et al, 2006), and because of its massive increase during mastitis it has been suggested as a biomarker for this disease (Larsen et al, 2010).…”
Section: Pathogen Differencesmentioning
confidence: 99%